Analisis Pengaruh Pengangguran, IPM dan PDRB terhadap Kemiskinan di Provinsi Sumatera Utara - Tina Angelia; Fitrah Maya Sari Hasugian; Joko Suharianto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Poverty is one of the problems still faced by various countries, including Indonesia. This study aims to analyze the effect of unemployment, Human Development Index (HDI), and Gross Regional Domestic Product (GRDP) on poverty in North Sumatra Province. The data used is secondary data obtained from the Central Bureau of Statistics (BPS) of North Sumatra during the period 2003-2024. The analysis method used is econometric analysis using the Ordinary Least Square (OLS) method with the help of Eviews 13 software. The results showed that partially, the variables of unemployment and HDI did not have a significant influence on poverty. However, GRDP has a significant negative effect on poverty, which indicates that an increase in GRDP can reduce the amount of poverty in North Sumatra Province. Simultaneously, unemployment, HDI, and GRDP have a significant influence on poverty with a contribution of 83.63%. These findings indicate that effective policies in reducing poverty need to focus on increasing GRDP and improving the quality of education and public health.